FRAUDULENT FINANCIAL REPORTING BASED OF FRAUD DIAMOND THEORY - Tarmizi Achmad; Imang Dapit Pamungkas (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2018)
The research aims to analyse whether external pressure, financial stability, financial targets, ineffective monitoring, rationalization and capability effect on fraudulent financial reporting. The population this study is banking company listed on the Indonesia Sctock Exchange with a total sample of 87 banking companies in 2011-2016. Based on the results of research using regression analysis, only external variables of incentive and financial targets have a positive effect on fraudulent financial reporting. Meanwhile, financial stability and capability have a negative impact on fraudulent financial reporting. Further, other variables such as ineffective monitoring and rationalization do not affect fraudulent financial reporting.